2022
DOI: 10.1007/s11010-022-04629-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of kaempferol and myricetin in streptozotocin-induced diabetes synergistically via modulation in pancreatic amylase, glycogen storage and insulin secretion

Abstract: Kaempferol and Myricetin alone have promising bene ts on diabetes and related complications, yet the effectiveness of cotreating the two compounds on diabetes have not been studied. The existing investigation was to study the combined anti-diabetic effect of kaempferol and myricetin in streptozotocin (STZ)-activated diabetes in rats. MethodsTo evaluate the antidiabetic activity, 36 Wistar rats were segregated into six groups; Normal, 50 mg/kg STZ-induced diabetes, and four (50 mg/kg kaempferol, 50 mg/kg myrice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…AgNPs. The α-amylase inhibition activity of kampeferol and gallic acid has recently been reported (93,94) Figure 12 shows the interaction of galantamine (std), kaempferol, gallic acid, and vallesamine with BchE. All interact with BchE active sites by conventional hydrogen bonds, carbon − hydrogen bonds, Pi − Pi stacking, and Pi − alkyl interactions.…”
Section: Molecular Dockingmentioning
confidence: 88%
“…AgNPs. The α-amylase inhibition activity of kampeferol and gallic acid has recently been reported (93,94) Figure 12 shows the interaction of galantamine (std), kaempferol, gallic acid, and vallesamine with BchE. All interact with BchE active sites by conventional hydrogen bonds, carbon − hydrogen bonds, Pi − Pi stacking, and Pi − alkyl interactions.…”
Section: Molecular Dockingmentioning
confidence: 88%
“…Like quercetin, myricetin (3,3 ,4 ,5,5 ,7-hexahydroxylflavone) is a flavonoid from the flavonol class that is present in various fruits and vegetables, nuts, berries, and beverages [279]. Animal and clinical studies revealed its hypoglycemic effect and ability to increase the sensitivity to insulin and enhance glycogen synthesis and glucose utilization, together with the prominent antioxidative and anti-inflammatory activities that are most likely essential for its protective effects against diabetic complications in various tissues [280][281][282][283][284][285]. Myricetin possesses five hydroxyl groups that underlie its potent antioxidative activity.…”
Section: Effects Of Other Flavonols On Diabetes-induced Cognitive Dec...mentioning
confidence: 99%